REMOVAL OF WAXY SUBSTANCES FROM FIBROUS WASTE FOR THE PREPARATION OF PAPER FURNISH FROM LOCAL RAW MATERIALS - Miratayev Abdumalik Abdumajidovich; Abdumajidov Anvar Abdumalikovich (International Journal of Innovations in Engineering Research and Technology, 2021)
The article presents the results of research on the separation of printing ink from MS-3 waste paper, its removal from the cellulose suspension, discoloration of the recycled fiber and increasing the degree of whiteness. The necessary conditions for the removal of waxy substances from waste paper have been recommended.